The Effectiveness of Pictionary Games as a Tool to Teach Vocabulary for Senior High School Students - Amelia Yustina Fatmawati; Delsa Miranty; Welliam Hamer (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2023)
This study investigates the effectiveness of Pictionary games as a tool to teach senior high school students vocabulary. In order to accomplish this purpose, this study was conducted in the 10th grade of a senior high school in Banten Province, Indonesia. The data used a quantitative research methodology by implementing a quasi-experimental research design. The population in this study was students of class a senior high school in Banten Province, Indonesia, and took 72 students as a sample divided into two classes. Cluster random sampling was used to select the class, and the result of random cluster sampling was obtained with 10 MIA 2 as the experimental class and 10 IIS 2 as the control class. The pre-test and post-test were selected as the research instrument to know the effectiveness of Pictionary games. The researchers used Normality and Homogeneity tests to analyze the study's data. After collecting the students’ pretest and post-test, the researchers measured the results to determine the effects on students’ vocabulary mastery between experimental and control groups. The post-test average of the experimental group is higher than the control group (8.392 > 5.054). It can be concluded that the Pictionary games effectively teach vocabulary in the 10th grade of a senior high school in Banten Province, Indonesia. It recommends that teachers significantly apply Pictionary games when teaching English to increase the student’s vocabulary mastery.